Epidemiological characteristics of hand, foot, and mouth disease clusters during 2016–2020 in Beijing, China. Issue 10 (17th June 2022) - Cui, Yan; Yang, Yan‐Na; Zheng, Ran‐Ran; Xie, Ming‐Zhu; Zhang, Wan‐Xue; Chen, Lin‐Yi; Du, Juan; Yang, Yang; Xi, Lu; Li, Hua; Li, Hong‐Jun; Lu, Qing‐Bin
Abstract: Hand, foot, and mouth disease (HFMD) is an infectious disease that usually occurs in children under 5 years and is caused by a group of enteroviruses. This study aimed to investigate the epidemiological characteristics of HFMD clusters from 2016 to 2020 in Tongzhou, Beijing, and explored the genetic evolution of CV‐A6. The HFMD case information came from the Information System of China Center for Disease Control and Prevention (CDC), as well as the clusters information verification and on‐site investigation by Tongzhou CDC. ARIMA model was applied to forecast HFMD clusters in 2020. Totally 440 HFMD clusters were reported during 2016–2020. The large peak of the clusters occurred in April–July, followed by a smaller peak in October–November during 2016–2019. However, in 2020, the two peaks disappeared. The main site of HFMD clusters was childcare facilities (65.0%) and mostly occurred in urban areas (46.1%). The detection rate of CV‐A6 was the highest (36.1%), and cases with CV‐A6 infection had the highest proportion of fever. The phylogenetic analysis based on CV‐A6 VP1 gene showed that the predominant strains mainly located in Group F during 2016–2017, while changed into Group A during 2018–2020. HFMD clusters presented seasonality, mainly located in childcare facilities and urban areas, and CV‐A6 was the major causative agent. Targeted prevention and control measures should be taken to reduce HFMD clusters.